Systematic Review Strategi Pengembangan Talenta dalam Era Digital: Membangun Sumber Daya Manusia Unggul di Masa Depan - Villany, Ershine; Solehudin, Solehudin; Nurhasanah, Nunung (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
In the fast-changing digital era, human capital (HR) has become a strategic asset for organisations to maintain competitive advantage. However, organisations face challenges in developing employee talent to deal with technological disruption, changing demographics and new skill needs. This study conducted a systematic review of the literature to identify talent development strategies that are effective in building superior human capital in the digital era. The results show that key strategies include digital skills development, identification of talent for digital initiatives, a culture of innovation and flexibility, utilisation of technology and data analytics in talent development, and a holistic and strategic approach. A combination of these strategies is needed to effectively face the challenges of the digital era, so that organisations can build excellent, adaptive and ready-to-face human resources for the changing business environment.